Uji Kelayakan terhadap Software Pembelajaran Computer Aided Design dalam Ragum Mini 3D - Rizal Rifaâ€˜Ã, Muhammad; Wahyudin; Nugraha, Billy (Infotekmesin, 2022)
One of the problems of lecture assignments based on drawing is drawing technique. The function of the learning software is to be the basic media of the teacher in explaining the material. This research aims to analyze the feasibility of learning software, namely computer aided design. Research techniques applied in this research are through reference sources from previous studies. The feasibility test method uses validity techniques that already have parameters in determining the feasibility of the test. Results from this study compared to the results of analysis from previous studies showed 78.6% (can be categorized as feasible). In addition, computer aided design learning software in 3D mini ragum has a validation result of 69% (can be categorized as feasible). Then it can be concluded that the learning software used today can support the delivery of materials that will be given.